1993
DOI: 10.1002/aic.690391206
|View full text |Cite
|
Sign up to set email alerts
|

Robust stability analysis of constrained l1‐norm model predictive control

Abstract: Sufficient conditions for robust closed-loop stability of a class of dynamic matrix control ( D M C ) systems arepresented. The I,-norm is used in the objective function of the on-line optimization, thus resulting in a linear programming problem. The ideas of this work, however, are expandable to other DMC-type controllers. The keys to the stability conditions are: to use an end-condition in the moving horizon on-line optimization; to have coefficients of the move suppression term in the objective function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(64 citation statements)
references
References 9 publications
1
61
0
2
Order By: Relevance
“…They show that, under certain assumptions, predictive control can stabilise plants when a terminal equality constraint is embedded in the optimisation problem; that is, it is required that the terminal state is at a point in the state space. Similar results also have been reported by Genceli and Nikolaou (1993) and Rawlings and Muske (1993). However, from the computational point of view, solving a nonlinear dynamic optimisation problem with equality constraints is highly computationally intensive and in many cases is impossible to perform within a limited time.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…They show that, under certain assumptions, predictive control can stabilise plants when a terminal equality constraint is embedded in the optimisation problem; that is, it is required that the terminal state is at a point in the state space. Similar results also have been reported by Genceli and Nikolaou (1993) and Rawlings and Muske (1993). However, from the computational point of view, solving a nonlinear dynamic optimisation problem with equality constraints is highly computationally intensive and in many cases is impossible to perform within a limited time.…”
Section: Introductionsupporting
confidence: 81%
“…This follows from modification of the standard argument; for example, see Genceli and Nikolaou (1993), Michalska and Mayne (1993), Chen and Allgöwer (1998).…”
Section: Stability and Feasibilitymentioning
confidence: 99%
“…(37) and (38) Following the preceding observations, it should be noted that the widespread practice of using a discount factor β may be more problematic than realized, in the sense that it may not result in robustly stabilizing strategies. This situation, namely the need to shape weights of the terms in the MPC objective in an increasing rather than decreasing fashion in order to ensure robustness, has been rigorously analyzed in the past (Genceli and Nikolaou, 1993;Vuthandam et al, 1995) and should be explored further.…”
Section: Taylor Rules and Resulting Closed-loop Stabilitymentioning
confidence: 99%
“…The associated Table 15 shows the resulting coefficient for the Taylor-like solution provided by MPC. Second, it has been rigorously shown that keeping m small improves the robustness of the closed loop, namely it helps maintain closed-loop stability in the presence of discrepancies between the model used by MPC and the actual system under control (Garcia and Morari, 1982;Genceli and Nikolaou, 1993;Vuthandam et al, 1995).…”
Section: A Choice Of Prediction Horizon Length Nmentioning
confidence: 99%
“…The most widely referenced approach to guarantee stability in MPC procedures is to add an equality constraint on the final state in the prediction horizon (a so called end-state constraint) or put a weight on the final state in the objective function (De Nicolao & Scattolini, 1998;Genceli & Nikolaou, 1993;Kwon & Pearson, 1977;Kwon & Byun, 1989;Mayne & Michalska, 1990;Thomas, 1975). Another approach is to use an infinite prediction horizon with a finite control horizon (Rawlings & Muske, 1993), making it possible to apply standard linear quadratic regulator (LQR) theory to guarantee stability (Kwakernaak & Sivan, 1972;Cheng & Krogh, 2001).…”
Section: State Space Model For Supply Layermentioning
confidence: 99%